Determinantes das irregularidades nos pregões eletrônicos da Prefeitura Municipal de Fortaleza - Furtado, Túlio de Queirós (2024)
Contracting in the public sector depends, as always, on a prior bidding procedure, where specific rules must be observed to ensure the selection of the most advantageous proposal, as well as ensuring broad participation and equal conditions among participants. The aforementioned norms become the essentially formal procedure and, therefore, dissolve, complex and costly. Having established these premises, this work aims to investigate the determinants of irregularities in tenders carried out by the Municipality of Fortaleza, in the electronic form of the notice, and in the end propose possible changes in an attempt to reduce the incidence of these events. To estimate this, a Logit model of the probability of occurrence of irregularities was used in a database formulated especially for this purpose where it was possible to distinguish variables related to the items/pregs traded (value, destination, number of competitors, economy, object, competitors) and the winning companies (size and location). The results show a very low risk of irregularities, but vary according to some indicators such as value, number of unpaid bids, year, destination and object.